Emotion, Ritual and Power in Europe, 1200–1920
XXI, 320 p.
Keywords: This volume spans the fourteenth to nineteenth centuries, across Europe and its empires, and brings together historians, art historians, literary scholars and anthropologists to rethink medieval and early modern ritual. The study of rituals, when it is alert to the emotions which are woven into and through ritual activities, presents an opportunity to explore profoundly important questions about people’s relationships with others, their relationships with the divine, with power dynamics and importantly, with their concept of their own identity. Each chapter in this volume showcases the different approaches, theories and methodologies that can be used to explore emotions in historical rituals, but they all share the goal of answering the question of how emotions act within ritual to inform balances of power in its many and varied forms. .